2021
DOI: 10.1007/s13555-021-00579-9
|View full text |Cite
|
Sign up to set email alerts
|

Itraconazole Oral Solution for a Case of Infantile Hemangioma: Monitoring the Efficacy by Dermoscopy and MRI

Abstract: Infantile hemangioma is a common and challenging benign vascular tumor. Although involution is spontaneous, approximately 10% of infantile hemangioma of large size or in specific locations may cause ulceration, severe cosmetic and functional problems that may require intervention. Treatment options include oral propranolol, topical timolol, and oral corticosteroids. However, the clinical response is not always satisfactory. We report the case of a 4-month-old boy who presented with an irregular erythematous pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Based on the method of orthogonal transformation, this method mainly generates the observation matrix through the transformation of the orthogonal matrix. The specific steps are as follows: form an N × N -dimensional orthogonal matrix, then take M rows from the matrix to obtain an M × N -dimensional matrix, and finally, normalize the column direction of the matrix to obtain the observation matrix [ 19 , 20 ]. At present, the observation matrix obtained by this method is mainly composed of the partial Fourier observation matrix and partial Hadamard observation matrix.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the method of orthogonal transformation, this method mainly generates the observation matrix through the transformation of the orthogonal matrix. The specific steps are as follows: form an N × N -dimensional orthogonal matrix, then take M rows from the matrix to obtain an M × N -dimensional matrix, and finally, normalize the column direction of the matrix to obtain the observation matrix [ 19 , 20 ]. At present, the observation matrix obtained by this method is mainly composed of the partial Fourier observation matrix and partial Hadamard observation matrix.…”
Section: Methodsmentioning
confidence: 99%
“… 29 , 30 In 2015, our team found that ICZ had a positive effect on the treatment of IH, which was further confirmed in later treatment practice. 13 , 14 Research also demonstrated that oral itraconazole can be an equivalent option for oral propranolol while safer and shorter treatment periods. 31 We found that ICZ can induce IH regression by downregulating the platelet-derived growth factor-D/PI3K/Akt/mTOR pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Our team has previously reported cases in which ICZ was used in infants with hemangioma. 13 , 14 Herein, we report a case of infantile cutaneous hemangioma complicated with hepatic hemangioma treated by oral ICZ solution. Dermoscopy and color ultrasound images play a vital role in the diagnosis and in the therapeutic efficacy monitoring.…”
Section: Introductionmentioning
confidence: 99%